f(x) = x2 + 2x + 1, g(x) = 11x − 19 x<span>2 </span>+ 2x + 1 = 11x - 19 x2 - 9x + 20 = 0 (x-4)(x-5) = 0 x = 4, 5
Answer:
Step-by-step explanation:
To find the zeros of this polynomial, set the polynomial equal to zero, and then set each of the factors equal to zero separately. Solve each equation for x:
x - 1 = 0 yields x = 1. The x-intercept is (1, 0).
x + 3 = 0 yields x = -3. The x-intercept is (-3, 0).
2x + 1 = 0 yields x = -1/2 The x-intercept is (-1/2, 0)
Answer:
y=-5x+4
Step-by-step explanation:
I'm assuming this is a Pythagorean theorem problem. If so the answer would be √125